2016
DOI: 10.1590/s0100-204x2016000900065
|View full text |Cite
|
Sign up to set email alerts
|

Soil aggregation according to the dynamics of carbon and nitrogen in soil under different cropping systems

Abstract: -The objective of this work was to evaluate total soil carbon and nitrogen, as well as their contents in particulate and mineral-associated C fractions; to determine C stock and sequestration rates in the soil; and to verify the effect of C and N contents on soil aggregation, using different crop rotations and crop sequences under no-tillage. The study was carried out for nine years in a clayey Oxisol. The treatments consisted of different cropping systems formed by the combination of three summer crops (cropp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
3
0
1
Order By: Relevance
“…While superficial soil total C and N contents found after legume or corn harvest exceeded those found by Seben Junior et al (2016) in no-tillage corn intercropped with legumes and Muchane et al (2020) in subhumid soils under an agroforestry system, they are similar to those described by Lira Junior et al (2020) after two years of a subhumid tropical legume-shrub-tree based silvopastoral system. This reinforces these legumes potential to contribute to the storage of C and N in these soils over time, without the need for nitrogen inputs, as also reported by Ambrosano et al (2009) for corn growing systems with velvet bean and sunn hemp, both traditional tropical green manures.…”
Section: Discussionsupporting
confidence: 85%
“…While superficial soil total C and N contents found after legume or corn harvest exceeded those found by Seben Junior et al (2016) in no-tillage corn intercropped with legumes and Muchane et al (2020) in subhumid soils under an agroforestry system, they are similar to those described by Lira Junior et al (2020) after two years of a subhumid tropical legume-shrub-tree based silvopastoral system. This reinforces these legumes potential to contribute to the storage of C and N in these soils over time, without the need for nitrogen inputs, as also reported by Ambrosano et al (2009) for corn growing systems with velvet bean and sunn hemp, both traditional tropical green manures.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, the first hypothesis, that wheat-maize rotation did not significantly increase SOC content, was rejected. This finding is similar to the results reported by Seben Junior et al [24], where the effect of crop rotation was lower than that of soybean monoculture and higher than that of maize monoculture in soybean-maize rotation versus monoculture.…”
Section: Effect Of Cropping System On Socsupporting
confidence: 92%
“…However, a study showed that the SOC content is higher in rice monocrops than in rice-wheat rotations [3]. Similar results have been observed under soybean cultivation, with SOC content being higher under monocropping than under soybean-maize rotation, and that under soybean monocropping, the SOC content was significantly higher than that under maize monocropping [24]. Did wheat-maize rotation and straw returning significantly affect soil organic carbon in the Sushui River Basin?…”
Section: Introductionmentioning
confidence: 68%
“…The benefit of chiseling in increasing TOC content in relation to no-tillage is attributed to incorporating plant material into the soil every other year, four times in nine years of study. This plant material is generally coarser than plant material incorporated in the conventional tillage, which favors the slow and gradual decomposition of the residue incorporated by the chiseling (Olson et al, 2016;Seben Junior et al, 2016). Chiseling does not fully expose the compost/residue to microorganism action and oxygen which accelerates the degradation process, and which usually occurs in conventional tillage, favoring the results observed in this treatment in the 0.00-0.05 m layer.…”
Section: Resultsmentioning
confidence: 90%
“…It is known that grasses have a primordial effect on soil structuring due to improved aggregation (Seben Júnior et al, 2016). However, diversified cover crops must be adopted to improve the soil physical quality; in this context legume insertion could improve the structural quality of the soil under no-tillage because their root system favors forming macropores (Seben Junior et al, 2016;Calonego et al, 2017;Reichert et al, 2017). Crop diversification is necessary for chiseling to be an effective management of the area.…”
Section: Resultsmentioning
confidence: 99%